Pengenalan Alfabet Sistem Isyarat Bahasa Indonesia (SIBI) Menggunakan Convolutional Neural Network - Thira, Indra Jiwana; Riana, Dwiza; Ilhami, Azriel Noer; Dwinanda, Brama Rizky Setia; Choerunisya, Hana (Institut Teknologi Garut, 2023)
Deaf is fourth in the list of persons with disabilities in Indonesia at 7.03%. Deaf people communicate using sign language both when communicating with fellow deaf people and with normal people. The problem that arises is that few normal people master sign language, especially the Indonesian Sign System (SIBI) so that it becomes an obstacle when they have to communicate with deaf people. This study aims to classify the alphabet in SIBI except the letters J and Z with a total of 24 classes. Classification is done by comparing three CNN architectures, namely MobileNetV2, MobileNetV3Small and MobileNetV3Large to get the best model. The results showed that the MobileNetV3Small architecture produced the best model at batch size 32 and the number of epochs 30 with an accuracy of 98.81% for testing data.